Thematic Analysis of the Hadith on Patience as a Coping Mechanism Against Life’s Pressures - Ardi Wahdana; Anwar Rasyidin; Nur Komalasari Putri (Yayasan Albahriah Jamiah Indonesia, 2025)
The increasing pressures of modern life, characterized by fluctuating social demands, economic instability, and rising psychological distress, call for more integrative coping strategies; however, the systematic study of patience in the hadith as a comprehensive coping framework remains underexplored, thus opening up new research opportunities. This study aims to analyze the representation of patience in the hadith thematically and interpret it as a coping mechanism encompassing emotional, cognitive-behavioral, and spiritual dimensions in dealing with life’s pressures. The method employed is qualitative research with thematic analysis, which involves selecting hadiths from the main books based on the relevance of the theme, initial coding, thematic categorization, and cross-disciplinary interpretation through Islamic psychology literature and coping theory to build an integrative understanding. The results of the study indicate three main themes: first, patience as emotional management, as evident in the hadiths regarding anger control, regulating affective responses, reducing impulsive reactivity, and establishing emotional stability; second, patience as a rationalization of adaptive actions, as evident in the hadiths that emphasize firmness in clear thinking, proportional assessment of difficult situations, strengthening realistic mindsets, and establishing constructive behavior; third, patience as the foundation of spiritual strength, through hadith that lead to positive meaning, value orientation, and inner peace that increase empowerment in facing stress. In conclusion, this study presents a new synthesis between thematic hadith studies and psychological coping models, offering both theoretical contributions and practical relevance for developing coping approaches tailored to the context of modern society.